THE POLICY OF ACEH GOVERNMENT IN DEVELOPING THE DAYAH TEACHER’S COMPETENCE AT ACEH – POST TSUNAMI - Zubaili Zubaili (State Islamic University of North Sumatra Indonesia, 2017)
Abstract. This study aimed to find out how the Government of Aceh's policy in developing the competence of Dayah teachers in post-tsunami Aceh through the Dayah Education Development Board of the Year 2008-2016, how the implementation of Aceh Government's policy in developing the competence of Dayah teachers in post-tsunami Aceh through the Aceh Dayah Education Development Board Year 2008 -2016, how the performance of Aceh Government policy in developing the competence of Dayah teacher in Aceh post Tsunami through Aceh Dayah Education Board Year 2008-2016, and how the support of Dayah leadership in the implementation of development of Dayah Teacher competence in Aceh post Tsunami through Aceh Dayah Education Board Year 2008-2016. The approach of this research is a qualitative approach, with data collection techniques using documentation, observation, and interview techniques. The analysis of this research uses three stages: data reduction, data display, and data verification and conclusion. And check the validity of data with Triangulation technique. The findings of the research indicate that (1) the development policy of Dayah Teacher Competency in the form of training program, apprenticeship, incentive giving, scholarship for Dayah teacher and addition of Arabic teacher, English for dayah. (2) Implementation of the development of Dayah Teacher competence has not been maximized due to the absence of special SOP on the development of competence of Dayah teachers. (3) The Implementation of the Implementation of the Development of Dayah Teacher Competence has not been optimal because of the lack of budget, it does not reflect the overall commitment. Local regulations on the development of Dayah teacher competence do not yet exist. (4) Dayah leaders strongly support the Government's policy. The study recommends the need to ask the Government of Aceh to establish sustainable policies in the development of Dayah teacher competence in Aceh by creating a qanun or special regulations on Dayah education as well as on the competency standards of Dayah teachers and Dayah leaders in Aceh.